Researching dance education post-2016: the global implications of Brexit and Trump on dance education. Issue 1 (2nd January 2018) - Rowe, Nicholas; Martin, Rose; Buck, Ralph; Anttila, Eeva
Abstract: The results of the 2016 British referendum on membership of the European Union and the presidential election in the United States of America initiated political changes that will arguably have resounding impacts, within and beyond the UK and the US for years to come. Much of the rhetoric accompanying these political victories appears to confront humanist ideals associated with inclusion, rationalism and transnational exchange. This article argues that these seismic political events in Europe and America will have an international impact on policies, practices and pedagogies associated with dance education, inevitably challenging those who seek to broaden meanings of socially, culturally, economically and politically inclusive arts education. We have gathered the queries of leading dance education researchers from around the world, to better understand how these political shifts are perceived, who feels they may be affected, how they feel it may affect them, and how research into dance education may respond to, and address, these effects. In doing so, we hope to provide a global snapshot of concerns felt by dance education academics in the aftermath of the 2016 British referendum and US Presidential election, and a research framework for investigating the implications of these events on dance education.